JENIS DAN DOMINASI MATERIAL YANG DIANGKAT OLEH TOWER CRANE PADA PEKERJAAN STRUKTUR (STUDI KASUS PROYEK RUMAH SAKIT MITRA KELUARGA SIDOARJO) - Naufal Hafidz Irsadunnafi (Jurnal Vokasi Teknik Sipil, 2024)
Development projects in Indonesia have progressed rapidly. One of the ongoing projects is the Mitra Keluarga Hospital Project (RSMK) Sidoarjo. Mitra Keluarga Hospital Project (RSMK) Sidoarjo was built with a building area of 14,330 m2 and has 6 floors + roof floor. In the implementation of the Mitra Keluarga Hospital Project (RSMK) Sidoarjo requires heavy equipment in the form of a tower crane which has a high mobility function as a supplier of materials and tools needed during construction. This study aims to determine the type and dominance of materials lifted by tower cranes in structural work. The method used is field observation which is carried out for 14 working days with 8 hours per day. From the observations obtained several types of materials lifted by the tower crane, namely reinforcing iron, UNP iron, hollow iron, plywood, suri-suri, tie rod + wing nut, push pull, bucket concrete, formwork, scaffolding, support pipes, galvanized pipes, rafters, beam clamps, column clamps, hanging formwork, welding machines, compressors, stirrups, bendrat wire, and reinforcement circuits. From the analysis of several materials raised, there are 3 dominant materials, namely D19 iron, D10 iron, and bucket concrete + ready mix.